Glycosaminoglycans and Proteoglycans - Barbara Mulloy (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Proteoglycans (PGs) are glycoconjugates in which a protein or peptide core is substituted with polysaccharide chains known as glycosaminoglycans (GAGs). The GAG sidechains carry a significant proportion of the functionality of PGs, interacting with many proteins to form structural units in the extracellular matrix and to modulate the transport and signalling of small proteins acting as morphogens, growth factors and cytokines. Purified GAGs such as heparin and hyaluronan are in common use as therapeutic agents, with many more PG-based natural products, synthetic and semi-synthetic mimetics on the way; in addition, potential therapeutic strategies involving PG/GAG biosynthesis and degradation as targets are currently in development.